The "Epulis" Dilemma. Considerations from Provisional to Final Diagnosis. A Systematic Review - Paola Costa; Matteo Peditto; Antonia Marcianò; Antonio Barresi; Giacomo Oteri (MDPI AG, 2021)
"Epulis" is a widely used term to describe a localized gingival enlargement. However, a wide range of neoformations might present as localized, slow-growing, asymptomatic gingival masses. A systematic review was conducted to outline the pathological entities that were provisionally dignosed as "epulis" and whose final diagnosis was made after microscopic examination. An electronic search of PubMed, Google Scholar and Scopus databases from January 2000 to February 2021 was performed. An initial search of the databases identified a total of 864 documents, and after a careful process of screening and selection, 14 studies were included in this systematic review and processed for data extraction. The results show that histological examination, sometimes combined with immunohistochemistry, might reveal a wide spectrum of lesions, including hamartomatous lesions, non-neoplastic lesions, benign and malign neoplasms and metastases from distant cancers.